Chemotherapy‐related cardiotoxicity: are Australian practitioners missing the point?. Issue 10 (9th October 2017) - Conyers, Rachel; Costello, Ben; La Gerche, Andre; Tripaydonis, Anne; Burns, Charlotte; Ludlow, Louise; Lange, Peter; Ekert, Paul; Mechinaud, Francoise; Cheung, Michael; Martin, Michelle; Elliot, David
Abstract: Background: It has long been established that cardiotoxicity occurs as a result of exposure to certain chemotherapeutics, particularly anthracyclines. Historically, clinicians equate cardiotoxicity with a poor prognosis, in a small percentage of patients and deem long‐term surveillance as optional. Emerging evidence suggests that anthracycline cardiotoxicity (ACT) is a life‐long risk with an incidence approaching 20%. Aims: To elucidate the incidence of anthracycline cardiotoxicity within a current paediatric oncology survivor cohort. Methods: Participants were identified through the Haematology‐Oncology database at the Royal Children's Hospital, Melbourne. Patients were identified from a retrospective audit of outpatient attendances between January 2008 and December 2015. Patients with a cancer diagnosis exposed to anthracyclines were eligible for the study. Patient demographics and echocardiogram findings were recorded with patients subcategorised according to degree of ACT. More significant ACT defined as fractional shortening (FS) <24% and less significant if FS 24–28% or a decline in baseline ejection fraction of >10%. Results: Two hundred and eighty‐six of a total 481 identified patients were eligible for study inclusion. Twenty patients displayed significant ACT with FS <24%. Ten patients had a FS 24–28% and 25 patients with a decline in ejection fraction from baseline of >10%. Overall, 6.6% demonstrated significant cardiac complications, whilst 19.6 % demonstrated some degree of ACT and decline in myocardial function. When stratified for cumulative anthracycline dose, the incidence of severe cardiac dysfunction was 5.1% (<250 mg/m 2 ) and 25% (>250 mg/m 2 ) Conclusion: This study demonstrates, in keeping with modern literature, the higher incidence of anthracycline associated cardiac toxicity and a need for better surveillance and follow up.